2017
DOI: 10.1038/s41598-017-04023-x
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of PD-L1 expression in patients with glioma: A meta-analysis

Abstract: A large number of studies have shown that programmed death-ligand 1 (PD-L1) is abnormally expressed in gliomas. However, the prognostic significance of PD-L1 expression in glioma patients remains unresolved. Accordingly, we conducted a meta-analysis to determine the prognostic role of high PD-L1 in patients with glioma. Electronic databases were searched to identify studies evaluating PD-L1 expression and overall survival (OS) in these patients. A total of 6 studies (published in 4 articles) that involved 1052… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 21 publications
0
52
0
Order By: Relevance
“…Some could argue that the tumors in the refractory Bev group were the recurrent tumors following not only Bev but also radiotherapy and temozolomide, and those therapies might also have affected the immunohistochemical results. However, the expression of PD-1 and PD-L1 was known to increase in recurrent glioblastomas, 16,29 and the results contrary to those were very likely due to the effect of Bev.…”
Section: Limitations Of the Studymentioning
confidence: 71%
See 2 more Smart Citations
“…Some could argue that the tumors in the refractory Bev group were the recurrent tumors following not only Bev but also radiotherapy and temozolomide, and those therapies might also have affected the immunohistochemical results. However, the expression of PD-1 and PD-L1 was known to increase in recurrent glioblastomas, 16,29 and the results contrary to those were very likely due to the effect of Bev.…”
Section: Limitations Of the Studymentioning
confidence: 71%
“…Programmed cell death ligand‐1 is frequently expressed in glioblastomas reportedly in 61%‐88% of tumor cells . Previous studies showed that high PD‐L1 expression correlated with worse OS in patients with glioblastoma . The expression of PD‐L1 is induced by various pro‐inflammatory molecules such as γ‐interferon and VEGF‐A in the tumor microenvironment .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, related research has reported the significance of PD-L1 expression on tumour tissues as an independent poor prognostic factor [57,58]. In this paper, we have investigated the clinical relevance of immune system biomarkers, TILs, TAMs, TBs, and PD-L1, in MIBC patient prognosis.…”
Section: Discussionmentioning
confidence: 98%
“…15,16 Importantly, PD-L1 and PD-L2 expression correlated with poor prognosis in different tumor types, including breast cancer, urothelial cancer, renal cancer, gastric cancer, melanoma, glioma, ovarian cancer, and lung cancer. [17][18][19][20] Tumor heterogeneity can present an additional mechanism of tumor cell escape from CAR T-cell therapies, as not all cells of a tumor might express sufficient levels of the targeted antigen to be recognized and eliminated by the CAR T cells. This phenomenon is called ''antigen loss,'' and relapses due to antigen loss may be prevented by simultaneously targeting two tumor antigens.…”
mentioning
confidence: 99%